Partial transient liquid phase diffusion bonding of ZrC-SiC and 304 stainless steel by Ti/Ni interlayer: Microstructure and properties. Issue 9 (August 2022) - Jincheng, Lin; Bangyang, Xiao; Lili, Xing; Yanying, Hu; Panpan, Lin; Tiesong, Lin; Peng, He; Weiqi, Yang
Abstract: The ZrC-SiC ceramic (ZS) was joined to 304 stainless steel (304SS) by using Ti/Ni interlayer. The joining process involves a transient liquid phase bonding at the ZS interface and a diffusion bonding at the 304SS interface. It is found TiCx grew fast on ZS interface or precipitated as particles in certain region of transient liquid, and its distribution and morphology were controlled by Ti gradient. Small amount of Si dissolved into liquid and then precipitated as Ti3 Ni2 Si with similar lattice structure to Ti2 Ni. During solid-state diffusion, the TiNi reaction layer quickly transformed to refractory TiNi3 layer with a small number of Kirkendall pores and Ni5 Zr phase at the TiNi3 /Ni boundary. The underlying mechanism of interfacial reactions and microstructure evolution were proposed. The maximum shear strength of 97 ± 10 MPa was achieved when joining at 960 °C for 3 h. The failure mainly occurred along TiNi3 /Ni boundary due to the presence of Kirkendall pores.